Industrial training report: Three O Enterprise / Nur Aini Najihah Roslan - Roslan, Nur Aini Najihah (Universiti Teknologi MARA, Perlis, 2023)
This Industrial Training Report is a thorough essence of my journey as an intern within 25 weeks, from March 1 until August 15 2023, in Three O Enterprise to complete my 6thsemester. This report aims to show my industrial training process throughout these 25 weeks, including industrial experience such as engaging with many people, adaptations to working in a natural industry environment, and knowledge and skills gained related to work and personal development. I attended the first day of my industrial training on March 1 2023 and was assigned under Mr. Muhammad Ilham bin Abd Latiff, the head of the logistics department. During these 25 weeks, I have been working as an intern for a marketing team responsible for handling the marketing plan on social media and managing the e-commerce platform. This Industrial Training Report includes my profile, company profile, training experience, SWOT analysis, discussion, recommendations, and conclusion. SWOT analysis will be used to evaluate the company's competitive position, which includes its strength, weakness, opportunity, and threat. This report will overview my performance during my industrial training while observing the company by doing the SWOT analysis, evaluating the performance of Three O, and giving concrete recommendations for further improvement. The strengths of Three O are providing medical scrubs at affordable prices and having a low cost of manufacturing products. As a new company in the market, Three O Enterprise still needs to improve its marketing skills, which is its weakness. In addition, changing customer behaviours and a significant shift to online shopping are the opportunity factors for Three O. The threats would be local competition and established local brands would challenge Three O.